Whole-head OPM-MEG enables noninvasive assessment of functional connectivity. Issue 7 (July 2021) - Jas, Mainak; Jones, Stephanie R.; Hämäläinen, Matti S.
Abstract : A recent paper by Boto et al . established reliability of noninvasive functional connectivity measurements with a new whole-head optically pumped magnetometer magnetoencephalography (OPM-MEG) system. This rapidly developing technology enables a conformal sensor array to accommodate different head sizes and opens up new avenues for experiments in more naturalistic settings.